Special Issue: Rock Burst Disasters in Coal Mines - Chen, Yulong; Zhang, Junwen; Chen, Jianhang; Deng, Xuejie (Energies (Basel), 2022)
[...]an in-depth understanding of the failure mechanism of rock bursts is of the utmost importance for the prediction, mitigation and control of geological disasters in deep underground mining and engineering projects. [...]we established a Special Issue of Energies on the subject area of “Rock Burst Disasters in Coal Mines” (https://www.mdpi.com/journal/energies/special_issues/RBD_CM), which closed on the deadline of 31 May 2022. According to the results of numerical modelling, pre-crack blasting at higher rock layers enables a cantilever roof cave in time, thereby reducing the risk of rock burst. [...]the proposed method was applied in an engineering case, and the effectiveness of this method for the prevention and control of multi-dynamics disasters was evaluated by field observations of the caving height of rock layers and micro-seismic monitoring. [...]a mechanical relationship model of a bolt-drawing, anchoring interface was established to obtain the equations of the axial force and obtain shear stress distribution, as well as the decreasing-load transfer law of the anchoring section of bolts.